Elemental Profiling with Reference to Metal Index to Study Pollutant Load in Northern River of India - Singh, Bhagat; Tyagi, Ram Naresh; Jindal, Anil (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Present light was to determine elemental load in Sirsa river ecosystem to know the concentration of toxicants in this Sutlej river’s tributary that act as a gutter for industrial effluents of Baddi region. The inductively coupled plasma mass spectroscopy was used to detect concentration of elements in the department of biochemical engineering and biotechnology at IIT Delhi and the collected data was further analyzed statistically using one way ANOVA at (p≤0.05) followed by post hoc Duncan’s test to predict degree of variations and comparative profile in Table 1. The application of metal index was also performed to estimate water quality and co-related it with health hazards. Variations in concentration of elements was reported near common effluent treatment plant on pollutant Nallah (S2) in deceasing order read as Mg>Na>Ca>B>Zn>Cu>Mn>Fe>Mo>Al>Tl>Se in ppb. The concentration of elements reported at S1, S2, S3 were within permissible limit of WHO and Bureau of Indian Standards, except the value of Boron, Magnesium and Thallium were exceeded these guidelines constantly at site S2 of study area.The metal index values at S1, S2 and S3 were 1.55, 5.80 and 2.57 respectively. The site S2 was affected strongly due to presence of elemental dust and un-treated waste water discharged by chemical industrial units of Baddi region. This site (S2) was nearer to common effluent treatment plant on the bank of Sirsa river and found to be unsuitable at all with more value of metal index. It was also viewed to adopt such scale indices to estimate drinking water quality with respect to concentration of elements after equal interval of time; as there may be seasonal change in the load of debris due to rate of pollutants dumping in the riverine ecosystem which is directly proportional to the content of elements. The load of pollutants in water system was underlined to know the impact of inorganic waste discharges on water quality of river in this region of Himachal Pradesh along industrial belt.